Strategi Peningkatan Inklusi Keuangan Syariah di Sekolah An-Nikmah Kamboja - Farhan Wardana Solin; Rahmayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze strategies for increasing Islamic financial inclusion at An-Nikmah School in Cambodia, an Islamic educational institution in a country with a Muslim minority population. The main challenge faced is students' limited practical understanding of and access to Islamic financial products. This research used a descriptive-qualitative case study approach. Data were collected through in-depth interviews, participant observation, and document analysis with 33 participants, including students, teachers, school administrators, parents, community leaders, and financial practitioners. The results reveal internal strengths in the form of a commitment to Islamic principles, as well as challenges such as limited learning resources and technological infrastructure. The resulting strategies include the development of an integrated curriculum, teacher training, a mini-finance laboratory, a family literacy program, and partnerships with regional Islamic financial institutions. Implementation requires a phased approach with a monitoring system and innovative learning technology. This research provides an empirical contribution to strengthening Islamic financial literacy in education in a Muslim minority country.